Two-dimensional structure of long-period pulsations at polar latitudes in Antarctica - Yagova, N.; Pilipenko, V.; Lanzerotti, L.; Engebretson, M.; Rodger, A.; Lepidi, S.; Papitashvili, V. (Journal of Geophysical Research: Space Physics, 2004)
Two-dimensional (2-D) statistical distributions of spectral power and coherence of polar geomagnetic variations with quasi-periods about 10 min are analyzed using data from magnetometer arrays in Antarctica. Examination of the 2-D patterns of spectral power and coherence shows the occurrence of significant variations in geomagnetic power levels but with low spatial coherence near the cusp projection and in the auroral region. At the same time, low-amplitude pulsations, which we coin Picap3 pulsations, are very coherent throughout the polar cap. The region occupied by coherent Picap3 pulsations is shifted toward local MLT night from the geomagnetic pole and is decoupled from the regions of auroral and cusp ULF activity. The spectral power varies with time at polar latitudes in a manner different from that at auroral latitudes. Diurnal variations of power at different stations at the same geomagnetic latitude exhibit different behavior depending on the station’s position relative to geomagnetic and geographic poles. This asymmetry is shown to be partly attributed to the variations of the ionospheric conductance. The primary source of polar pulsations is probably related to intermittent magnetosheath turbulence and tail lobe oscillations, though a particular propagation mechanism has not as yet been identified Published A03222 1A. Geomagnetismo e Paleomagnetismo JCR Journal restricted